Finding Common Ground: Combining participatory action research and critical service-learning to guide and manage projects with Aboriginal communities - Johnston, Michelle; Bennett, Dawn; Mason, Bonita; Thomson, Chris (Springer, 2015)
In this chapter we argue that critical service learning can be a powerful and effective means of developing higher education students’ Indigenous cultural awareness and understanding. When done well, critical service learning also encourages reflection on the socio-political and environmental contexts that influence contemporary culture and contribute to social injustice. We support our argument with the example of a Western Australian service-learning program in which undergraduate media students worked with city based Aboriginal community groups over the course of a semester. This project is of special significance because of its use of participatory action research to assist students develop relationships with their community partners and to manage individual projects. The findings expose the common ground shared by critical service learning and participatory action research, and suggest that the principles of action research can contribute to a strong and successful service learning experience.